1999
DOI: 10.1088/0029-5515/39/11y/302
|View full text |Cite
|
Sign up to set email alerts
|

High performance experiments in JT-60U reversed shear discharges

Abstract: The operation of JT-60U reversed shear discharges has been extended to a high plasma current, low q regime keeping a large radius of the internal transport barrier (ITB), and a record value of equivalent fusion multiplication factor in JT-60U, QDTeq = 1.25, has been achieved at 2.6 MA. Operational schemes to reach the low q regime with good reproducibility have been developed. The reduction of Zeff was obtained in the newly installed W shaped pumped divertor. The β limit in the low qmin regime, which li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
110
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 15 publications
5
110
0
Order By: Relevance
“…A similar regime was also discovered in the DIII-D tokamak 3 at about the same time and has since been studied in several tokamaks, including JT-60U 4 and the Joint European Torus ͑JET͒. 5 Although it is produced by a different heating method, namely neutral beam injection, the ERS regime has strong similarities to two other regimes of improved confinement involving modification of the q profile, namely the pellet enhanced performance mode in JET 6 and that occurring in Tore-Supra with lower-hybrid current drive.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…A similar regime was also discovered in the DIII-D tokamak 3 at about the same time and has since been studied in several tokamaks, including JT-60U 4 and the Joint European Torus ͑JET͒. 5 Although it is produced by a different heating method, namely neutral beam injection, the ERS regime has strong similarities to two other regimes of improved confinement involving modification of the q profile, namely the pellet enhanced performance mode in JET 6 and that occurring in Tore-Supra with lower-hybrid current drive.…”
Section: Introductionsupporting
confidence: 63%
“…Similar difficulty in achieving q min Ͻ2 has also been experienced by the JT-60U team developing reversed-shear plasmas in that device. 4 Once a reliable startup had been developed, it was found that ERS transitions resulting in an improvement in global confinement, such as those observed at 1.6 MA, did not occur spontaneously under similar conditions at high current, possibly because the threshold power for the transition had increased beyond the available NBI power. ͑The peak deuterium NBI power available for ERS studies has been limited to about 29 MW because a longer total NBI heating duration is required in this mode of operation to span the prelude and postlude phases.͒ However, the transient formation of regions of increased gradient in the temperature profiles, particularly of the electron temperature, as opposed to the density profile, was observed in some 2.2 MA reversed-shear plasmas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…minor radius > local minimum at ρ ~ 0.6. ITBs which only exist at minor radius < local (or absolute) minimum, generate a peak in the bootstrap current profile at a smaller radius than is required for alignment with the peak in the total current density profile, resulting in a progressive shrinking of the ITB radius {see, for example, [14,15]}. The observation of ITBs extending into the positive magnetic shear region has been made on several tokamaks, with monotonic q-profiles such as in [16,17]; and in q-profiles with strong shear reversal in the core, such as in [2].…”
Section: Fully Noninductive Operationmentioning
confidence: 99%
“…If the same conditions had been realised in deuterium-tritium plasmas, it would, have resulted in a Q value of about 1.25, i.e. conditions better than breakeven [12].…”
Section: -Progress In Recent Yearsmentioning
confidence: 98%